2017
DOI: 10.1111/cyt.12508
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repeat FNA in non‐diagnostic and indeterminate thyroid nodules: A 5‐year single‐centre experience

Abstract: Repeat aspiration of non-diagnostic and indeterminate thyroid nodules had a positive impact in both groups, with diagnostic resolution rates of 80% and 75%, respectively. The present study therefore endorses the use of such strategy for the initial follow-up of nodules with no definite diagnosis, especially in low-resource centres with limited access to modern molecular technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…The small number of patients with surgical follow-up data did not allow significant comparison of the risks of malignancy between the two groups (≤ vs more than 3 months for repeat aspiration) studied. published data, 3,7,9,10,12,[18][19][20]24,28 and endorses the use of such technique in the management of these nodules, with reported changes to another TBSRTC categories in up to 85% and 94% of ND and AUS/ FLUS nodules, respectively. 25 The optimal timing for a repeat procedure, however, has been a source of debate.…”
Section: Histological Correlationmentioning
confidence: 74%
See 2 more Smart Citations
“…The small number of patients with surgical follow-up data did not allow significant comparison of the risks of malignancy between the two groups (≤ vs more than 3 months for repeat aspiration) studied. published data, 3,7,9,10,12,[18][19][20]24,28 and endorses the use of such technique in the management of these nodules, with reported changes to another TBSRTC categories in up to 85% and 94% of ND and AUS/ FLUS nodules, respectively. 25 The optimal timing for a repeat procedure, however, has been a source of debate.…”
Section: Histological Correlationmentioning
confidence: 74%
“…Although molecular analysis has been advocated for some of the cases initially classified as AUS/FLUS, repeat aspiration is still the preferred method to achieve a diagnosis in most of the instances, as well as for ND results, with a further aspiration yielding a definitive diagnosis in the majority of the cases 17‐20 . The optimal timing for rFNA, however, has been a source of extensive debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to examine serum calcitonin and CEA in patients who are highly suspected to be MTC. In addition, ultrasound‐guided fine needle aspiration biopsy (FNAB) is one of the most useful and accurate methods in the diagnosis of thyroid carcinoma with good sensitivity and specificity and optimal concordance to the final postoperative pathology . FNA is also an approved modality for the diagnosis of MTC with high sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…the final postoperative pathology. 26,27 FNA is also an approved modality for the diagnosis of MTC with high sensitivity. 28,29 Dyhdalo et al reported that in 61 cases of MTC that had both a preoperative FNAB and a thyroidectomy, MTC was diagnosed correctly in 86% (44/ 51).…”
mentioning
confidence: 99%